Russia’s Exogenous Factor in the Donbass Conflict - Ryabinin, Yevgeny (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2020)
The hypothesis of this research is that Russia has been imposing its influence on Ukraine since the collapse of the Soviet Union. Before the political and military crisis in 2013, it was an indirect influence, whereas since 2014 it has been a direct impact in many spheres. It is necessary to underline that Ukraine has always been split into two parts in terms of foreign policy priorities, language, religion, and culture. This fact was mentioned by Samuel Huntington, who predicted an intense crisis in bilateral relations between Russia and Ukraine in his work Clash of Civilizations. There were two parties in Ukraine that were widely supported in South-Eastern Ukraine, namely the Party of Regions and the Communist Party. The former never spoke about the integration of Ukraine as part of Russian integrational projects because its politicians were afraid of aggressive Russian capital. So they only used pro-Russian rhetoric to win elections. The Communist Party openly backed integration with Russia, but didn’t get enough support as for this idea. It is also demonstrated that there were no parties that were backed financially by Russia, because the parties that offered a kind of a union with Russia never got any seats in the parliament. Since 2014, Russia has been imposing its influence on Ukraine in various spheres, such as economics, politics, diplomacy, the military sphere, etc. Having signed two cease-fire agreements, Russia and Ukraine have failed to apply them and the crisis continues to this day.

W badaniu postawiono hipotezę mówiącą o wpływie wywieranym przez Rosję na Ukrainę od czasu rozpadu Związku Radzieckiego. Przed kryzysem polityczno-wojskowym w 2013 r. był to wpływ pośredni, a po 2014 r. przerodził się w wielu sferach we wpływ bezpośredni. Należy podkreślić, że ze względu na priorytety polityki zagranicznej, język, religię i kulturę Ukraina zawsze była podzielona na dwie części. Wspomniał o tym S. Huntington, który w swoim „Zderzeniu cywilizacji” przewidział intensywny kryzys w stosunkach dwustronnych między Rosją i Ukrainą. Na Ukrainie istniały dwie partie, które uzyskały szerokie poparcie w południowo-wschodniej Ukrainie, mianowicie Partia Regionów i Partia Komunistyczna. Partia Regionów nigdy nie mówiła o integracji Ukrainy w ramach rosyjskich projektów integracyjnych, ponieważ jej politycy obawiali się agresywnego kapitału Rosji. Aby wygrywać wybory posługiwali się jedynie retoryką prorosyjską. Partia Komunistyczna natomiast otwarcie popierała integrację z Rosją, ale nie uzyskała wystarczającego poparcia dla tego pomysłu. Udowodniono też, że żadne partie nie były wspierane finansowo przez Rosję, ponieważ partie, które oferowały coś w rodzaju unii z Rosją, nigdy nie uzyskały mandatów w parlamencie. Od 2014 roku Rosja narzuca Ukrainie swoje wpływy w różnych sferach, takich jak ekonomia, polityka, dyplomacja, sfera wojskowa itp. Po podpisaniu dwóch porozumień o zawieszeniu broni Rosja i Ukraina nie zdołały ich zrealizować, wobec czego kryzys wciąż trwa.
Rosja – zewnętrzny czynnik konfliktu w Donbasie
Keywords: Russia; Ukraine; separatism; Donbass; rebellious; DPR; LPR; Rosja; Ukraina; separatyzm; Donbas; zbuntowany; DRL; ŁRL